Genome-Wide Sequence Variation among Mycobacterium avium Subspecies paratuberculosis Isolates: A Better Understanding of Johne’s Disease Transmission Dynamics - Hsu, Chung-Yi; Wu, Chia-wei; Talaat, Adel M. (Frontiers in Microbiology, 2011)
Mycobacterium avium subspecies paratuberculosis (M. ap), the causative agent of Johne’s disease, infects many farmed ruminants, wild-life animals, and recently isolated from humans. To better understand the molecular pathogenesis of these infections, we analyzed the whole-genome sequences of several M. ap and M. avium subspecies avium (M. avium) isolates to gain insights into genomic diversity associated with variable hosts and environments. Using Next-generation sequencing technology, all six M. ap isolates showed a high percentage of similarity (98%) to the reference genome sequence of M. ap K-10 isolated from cattle. However, two M. avium isolates (DT 78 and Env 77) showed significant sequence diversity (only 87 and 40% similarity, respectively) compared to the reference strain M. avium 104, a reflection of the wide environmental niches of this group of mycobacteria. Within the M. ap isolates, genomic rearrangements (insertions/deletions) were not detected, and only unique single nucleotide polymorphisms (SNPs) were observed among M. ap isolates. While more of the SNPs ( 100) in M. ap genomes were non-synonymous, a total of 6,000 SNPs were detected among M. avium genomes, most of them were synonymous suggesting a differential selective pressure between M. ap and M. avium isolates. In addition, SNPs-based phylo-genomics had a enough discriminatory power to differentiate between isolates from different hosts but yet suggesting a bovine source of infection to other animals examined in this study. Interestingly, the human isolate (M. ap 4B) was closely related to a M. ap isolate from a dairy facility, suggesting a common source of infection. Overall, the identified phylo-genomes further supported the idea of a common ancestor to both M. ap and M. avium isolates. Genome-wide analysis described here could provide a strong foundation for a population genetic structure that could be useful for the analysis of mycobacterial evolution and for the tracking of Johne’s disease transmission among animals.